(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article looks at the legal and ethical issues arising from scientific ad-vances in the fields of bioarchaeological and forensic research on human bones. While DNA-based technologies allow methods of identification that were unthinkable just decades ago, the question arises as to whether legislation and guidelines govern-ing such research are keeping pace with developments. Similarly, new social concerns continue to emerge, as seen for example in the growth of migration and the associ-ated cultural differences. Comparing the legal situation in two civil-law countries (Ita-ly and Norway) and two common-law countries (the UK and the US), we come to the conclusion that – though maybe desirable – no legislation (hard law) is able to cover all legal and ethical aspects of such research, and that soft law in the form of guide-lines, codes of conduct and codes of ethics will continue to fill the legislative gaps. In the same vein, enforcement of these legal and ethical frameworks in the field of re-search would seem to be more in the hands of ethics committees than of the courts.